2014
DOI: 10.13109/prkk.2014.63.9.699
|View full text |Cite
|
Sign up to set email alerts
|

Mentalisierung und Bindungstransmission

Abstract: The present study was investigating the predictive role of maternal mentalizing and general as well as depressive symptom burden for attachment security at the end of the first year on a sample of 44 mother-child-dyads from a low-risk community study. Maternal mentalizing was assessed in a multidimensional way as Reflective Functioning (off-line) and Mind-Mindedness (on-line). The design was longitudinal measuring maternal Mind-Mindedness from a videotaped mother-child-play-interaction at the age of three mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Caregivers vary in their attachment security and ability for affect-centered mentalization, and thus in their ability to correctly interpret, mirror, and adequately or “contingently” respond to an infant’s affective signals and needs [ 50 ]. This has been shown to affect infant attachment [ 51 56 ], implicating consequences for the development of affect-centered mentalizing as well. Attachment relationships characterized by traumatic experiences such as emotional, physical, or sexual abuse are assumed to have particularly far-reaching consequences concerning the development of emotional self-awareness and affect regulation: in such cases, the caregiver, needed as a psychological safe haven, is a source of danger at the same time, creating a so-called “fright without solution” situation for the child [ 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…Caregivers vary in their attachment security and ability for affect-centered mentalization, and thus in their ability to correctly interpret, mirror, and adequately or “contingently” respond to an infant’s affective signals and needs [ 50 ]. This has been shown to affect infant attachment [ 51 56 ], implicating consequences for the development of affect-centered mentalizing as well. Attachment relationships characterized by traumatic experiences such as emotional, physical, or sexual abuse are assumed to have particularly far-reaching consequences concerning the development of emotional self-awareness and affect regulation: in such cases, the caregiver, needed as a psychological safe haven, is a source of danger at the same time, creating a so-called “fright without solution” situation for the child [ 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several other studies report no associations between PRF or RF and MM. Böhmann et al (2014) found no significant associations between MM assessed with mothers and infants at 3 months of age and later RF (assessed with the AAI) at about 12 months of age. Finally, Dollberg (2022) recently reported no significant associations between PRF and MM in a sample of mothers and their 3-month-old infants.…”
Section: Mentalizing In Offline and Online Contextsmentioning
confidence: 57%
“…While a handful of studies have examined associations between PRF and MM at varying time points (e.g., Arnott & Meins, 2007; Böhmann et al, 2014; Colbeck, 2014), the present study appears to be one of the first to examine concurrent and longitudinal cross-lagged associations between PRF and MM. Specifically, PRF at the initial assessment predicted greater appropriate MM and less nonattuned MM at T2, although there were no other significant cross-lagged associations at other time points.…”
Section: Discussionmentioning
confidence: 85%